Chemistry Tryout Instrument of the PPG BGT: A Pedagogical Content Knowledge Framework - Oktavia Sulistina; Nazriati (Department of Chemistry, Universitas Negeri Malang, 2026)
This study aims to develop chemistry tryout assessments for the Teacher Professional Education Program (PPG) for Specific Teachers (BGT) as an effort to improve the quality of assessment and enhance teachers’ readiness in facing examinations. The research was conducted using development and research procedures adapted to the characteristics of the product, namely an assessment instrument. The product generated consists of 11 chemistry tryout items test for PPG BGT, which have been tested for quality through content validation and empirical validation. The developed questions are based on Pedagogical Content Knowledge (PCK) and refer to the four core competencies of PPG graduates. The question formats include simple multiple-choice and complex multiple-choice items, all of which were found to be valid and high reliability.